(untitled) (Research, Society and Development, 2024)
Introduction: The great participation of technologies in different areas of everyday life is undeniable, and these technologies are continually introduced to children early, especially in the initial phase of development. This period is recognized as the period of greatest brain malleability, which allows learning to be favored through external stimuli and the development of various skills. In this sense, it is highlighted that the excessive and unruly use of screens is listed as a risk factor for interference with neuropsychomotor improvement. Objective: To describe the consequences of using digital screens for children’s cognitive development. Methodology: This is an integrative review of literature from the last 10 years, on the platforms: Scielo, Lilacs and MEDLINE. Literature review: The unregulated use of technology affects children and has a clear impact on cognitive development in childhood, such as intellectual disabilities, attention deficit, speech difficulties, psychological complications, such as depression and anxiety. Furthermore, it may be related to the increase in cases of childhood obesity, nutritional deficiencies, metabolic changes and sleep disorders. The use of screens was positive for child development when used for playful activities and active learning. Conclusions: Excessive use of digital screens can have several consequences on neuropsychomotor development, in addition to harming physical and mental health, increasing the likelihood of childhood sedentary lifestyle and failure to develop motor and communicative skills. Therefore, it can contribute to the emergence of diseases such as obesity and depression.